2022
DOI: 10.3389/fmolb.2022.1023031
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the H+/ATP coupling ratio by ADP and ATP as a possible regulatory feature in the F-type ATP synthases

Abstract: F-type ATP synthases are transmembrane enzymes, which play a central role in the metabolism of all aerobic and photosynthetic cells and organisms, being the major source of their ATP synthesis. Catalysis occurs via a rotary mechanism, in which the free energy of a transmembrane electrochemical ion gradient is converted into the free energy of ATP phosphorylation from ADP and Pi, and vice versa. An ADP, tightly bound to one of the three catalytic sites on the stator head, is associated with catalysis inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…To explain these data, the concept of two interconvertible states of ATP synthase, differing by their coupling ratios, was introduced. It has been suggested that the state with higher coupling ratios favors the binding of ADP, and the state with lower coupling ratios favors ATP binding [ 106 ].…”
Section: Paracoccus Denitrificans As a Unidirectional F ...mentioning
confidence: 99%
“…To explain these data, the concept of two interconvertible states of ATP synthase, differing by their coupling ratios, was introduced. It has been suggested that the state with higher coupling ratios favors the binding of ADP, and the state with lower coupling ratios favors ATP binding [ 106 ].…”
Section: Paracoccus Denitrificans As a Unidirectional F ...mentioning
confidence: 99%
“…As previously reported (Hirono‐Hara et al, 2001 ; Kobayashi et al, 2020 , 2023 ), F 1 showed initial rapid ATP hydrolysis, followed by gradual deceleration to reach the steady‐state catalysis. This time‐dependent inactivation is due to the ADP inhibition, where F 1 molecules transiently lapse into an inactive state during catalysis (Figure S2 and Table S3 ; Lapashina & Feniouk, 2018 ; Turina, 2022 ). After confirming the steady‐state catalysis of F 1 , that is, 180 s after F 1 injection, IF 1 inhibition measurement was initiated by adding IF 1 into the reaction cuvette.…”
Section: Resultsmentioning
confidence: 99%
“…As previously reported (Hirono-Hara et al, 2001;Kobayashi et al, 2020Kobayashi et al, , 2023, F 1 showed initial rapid ATP hydrolysis, followed by gradual deceleration to reach the steady-state catalysis. This time-dependent inactivation is due to the ADP inhibition, where F 1 molecules transiently lapse into an inactive state during catalysis (Figure S2 and Table S3; Lapashina & Feniouk, 2018;Turina, 2022).…”
Section: If 1 Inhibition In Wild-type Bmf 1 and Tfmentioning
confidence: 99%